The Urgency of Policy, Regulator and Risk Management in Maintaining a Sustainable Business: Case Study of Silicon Valley Bank (SVB) - Solikhawati, Anisa; Rasyidi, Ekky; Ahsan, Muhamad (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This study aims to analyze the urgency of policies, regulators, and risk management in maintaining business at one of the 16th largest banks in the USA, namely Silicon Valley Bank . The method used is descriptive quantitative method. The data used is secondary data in the form of financial reports from 2020 to 2022 and is enriched by qualitative data sourced from articles from 2019 to 2023. The results show that SVB's financial management has experienced an impairment in the ROA, NIM and CAR ratios. SVB has an urge or tendency to take very high risks in an effort to achieve large profits which result in the use of high leverage and unstable sources of funding. The urgency of policies, regulators and risk management is considered very high in the case of SVB because their overall role is in maintaining a sustainable business.